2020
DOI: 10.1016/j.eucr.2019.101035
|View full text |Cite
|
Sign up to set email alerts
|

A large epithelioid angiomyolipoma of the kidney in a very young child with idiopathic chylothorax: A diagnostic dilemma

Abstract: Epithelioid angiomyolipoma (EAML) is a subtype of angiomyolipoma, the most common benign renal tumour and usually asymptomatic until adulthood.This paper reports a patient with EAML identified at 30 months, the youngest age of presentation with this tumour reported in the literature. In this case the tumour was extremely large andwas successfully surgically removed. Furthermore, the patient had no other TS features, presented with acute symptoms, and had bilateral idiopathic chylothorax which was managed by oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…War has affected the medical sector throughout years of war as the direct damage of war to the medical centre and indirectly from physicians leaving the country (14). The nancial hurdles also directly affected healthcare quality as proper tests and treatment may be delayed or not conducted despite having skilled physicians (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…War has affected the medical sector throughout years of war as the direct damage of war to the medical centre and indirectly from physicians leaving the country (14). The nancial hurdles also directly affected healthcare quality as proper tests and treatment may be delayed or not conducted despite having skilled physicians (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies lacked proper funding which ultimately generated limited data. There are many crucial investigations not conducted in most studies in Syria, and delayed treatment can occur due to the nancial hurdles which can dramatically affect patients' care (12)(13)(14)(15)(16). This re ects some of the negative outcomes that Syrians have endured, especially in those who were mostly affected by the war.…”
Section: Outcomes Of the Psychological Burdenmentioning
confidence: 99%
“…Many studies suffered from a lack of funding which ultimately generated limited data. There are many crucial investigations not conducted in most studies in Syria, and delayed treatment can occur due to the nancial hurdles which can affect patients' care dramatically (12)(13)(14)(15)(16). This re ects some of the negative outcomes that Syrians have endured, especially those who were affected by the war.…”
Section: Outcomes Of the Psychological Burdenmentioning
confidence: 99%
“…It also correlated with their different demographic and war-related variables. This study used self-reported questionnaires in light of lack of funding that medical research in Syria is facing and unavailable resources for proper diagnosis (12)(13)(14)(15)(16). This study also assessed for other variables and compared them with other studies for a better evaluation of the mental disorders among Syrians and refugees.…”
mentioning
confidence: 99%